Local government conditional grants the seal of good local governance and the performance challenges fund - Diokno-Sicat, Charlotte Justine (Philippine Journal of Development, 2022)
The Philippine government provides conditional grants to local government units (LGUs) for certain priorities, such as budgetary allocations from national government programs. Other conditional grants depend on the LGUs’ (1) matching counterpart spending and (2) requirements or characteristics. An example of the latter is the Performance Challenge Fund (PCF). In the past decade, conditional grant programs have helped elicit an improved level of governance among LGUs. Eligibility to the PCF depends on the level of governance defined by the Seal of Good Local Governance (SGLG). On top of the eligibility requirements, the PCF mandates that it must be spent for identified national government priorities. This study examines the views of municipal development planning officials on the conditional grant program based on a survey of 1,373 municipalities. The results are intended to guide policymakers in the implementation of the SGLG Act of 2019.